2003
DOI: 10.1002/jcc.10347
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies for structures and energetics of RgnN2O (RgHe, Ne, Ar) clusters

Abstract: Minimum-energy structures of the Rg(2)-N(2)O (Rg=He, Ne, Ar) clusters have been determined with ab initio MP2 optimization, whereas the minimum-energy structures of the Rg(n)-N(2)O clusters with n = 3-7 have been obtained with the pairwise additive potentials. Interaction energies and nonadditive three-body effects of the Rg(2)-N(2)O ternary complex have been calculated using supermolecule method at MP4 and CCSD(T) levels. It was found from the calculations that there are two minima corresponding to one distor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…4 Species such as CO 2 , OCS, N 2 O, and CS 2 belong to a class and have similar properties, due to their isovalent electrons. Except for Rg-CS 2 (Rg = He, Ne, Ar, Kr, and Xe) complexes, the complexes consisting of such species (CO 2 , a) Electronic addresses: zhenglimin@wipm.ac.cn; cxduan@phy.ccnu.edu.cn; yplu@ntu.edu.sg OCS, N 2 O) and rare gas atoms have received much attention in both experimental [5][6][7][8][9][10][11][12] and theoretical studies, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] due to their fundamental nature and practical importance. In experiment, the microwave and infrared spectra for these complexes were reported widely [8][9][10][11][12] and showed that each complex has a T-shaped structure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Species such as CO 2 , OCS, N 2 O, and CS 2 belong to a class and have similar properties, due to their isovalent electrons. Except for Rg-CS 2 (Rg = He, Ne, Ar, Kr, and Xe) complexes, the complexes consisting of such species (CO 2 , a) Electronic addresses: zhenglimin@wipm.ac.cn; cxduan@phy.ccnu.edu.cn; yplu@ntu.edu.sg OCS, N 2 O) and rare gas atoms have received much attention in both experimental [5][6][7][8][9][10][11][12] and theoretical studies, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] due to their fundamental nature and practical importance. In experiment, the microwave and infrared spectra for these complexes were reported widely [8][9][10][11][12] and showed that each complex has a T-shaped structure.…”
Section: Introductionmentioning
confidence: 99%
“…(2), we determined the minimum‐energy structures for ( p ‐H 2 ) N –N 2 O clusters with N = 2–17. Similar to our previous work on Rg N –N 2 O,27 we focused on the minima corresponding to a sequential series of topologically related clusters. Accordingly, we used the conformation of ( p ‐H 2 ) N ‐1 –N 2 O as the initial guess of ( p ‐H 2 ) N –N 2 O.…”
Section: Resultsmentioning
confidence: 52%
“…The incremental shift then increases significantly, to 0.233 cm À1 , if our tentative band origin for Ar 3 -N 2 O is correct. It is worth noting that, even though the three Ar atoms in Ar 3 -N 2 O likely have equivalent positions relative to N 2 O, they are no longer necessarily equivalent to each other, since one may be located between the other two [41]. Still, the apparent nonlinearity of the shift for Ar 3 -N 2 O is slightly surprising and indicates that further studies of this cluster would be of interest.…”
Section: Vibrational Shiftsmentioning
confidence: 85%
“…So the fact that the change in the magnitude of the incremental shift is opposite for Ar n -CO 2 and-N 2 O may be rationalized by noting that the direction is the same: that is, in both cases adding a second argon atom gives slightly more blue-shift than expected from linearity. Sperhac et al [20] have discussed in detail the nonlinearity of the vibrational shifts for Ar n -CO 2 in the context of three body forces, and a number of subsequent theoretical studies have been published on this subject [41][42][43][44][45].…”
Section: Vibrational Shiftsmentioning
confidence: 99%